Distributed leader-follower consensus tracking control for fixed-wind uavs with positive linear speeds under directed graphs. Issue 5 (2020) - Peng, Xiuhui; Wang, Qishao; Xiong, Shixun
Abstract: This paper addresses the distributed leader-follower consensus tracking control problem of multiple fixed-wing uavs under directed graphs. A two-stage control structure, which can ensure the designed liner speeds always positive, is proposed. Using the position errors and the constructed intermediate attitude, the leader-follower consensus tracking controller is proposed under directed graph, when the leader's states available to each follower. Thereafter, based on this proposed control structure, the distributed leader-follower consensus tracking controller with the distributed observer is proposed, in which only a subset of followers have access to the leader's information. Finally, the numerical simulations are provided to validate the effectiveness of the proposed controllers.